Impact of atmospheric non-thermal plasma and hydrothermal treatment on bioactive compounds and microbial inactivation of strawberry juice: A hurdle technology approach. (January 2020) - Mehta, Deepak; Yadav, Sudesh Kumar
The aim of this study was to investigate the hurdle effect of combining atmospheric cold plasma (ACP) with hydrothermal treatment on ascorbic acid, individual polyphenolic compounds, total phenolic content, and microbial inactivation of strawberry juice. Strawberry juice was treated with ACP for 10 and 15 min using dielectric barrier discharge at 60 kV with the input voltage of 260 V. The ascorbic acid concentration was retained maximum only in ACP treatment followed by ACP + hydrothermal treatment. Furthermore, ACP treatment for 10 min coupled with hydrothermal treatment resulted in the higher concentration of gallic acid, epigallocatechin, phloretin, naringin, hyprin, and 4-O-caffeoylquinic acid with respect to control ( p  < 0.05). In addition, ACP treatment for 10 min at 60 kV in combination with hydrothermal treatment resulted in increased total phenolic content ( p  < 0.05). Moreover, a 2-log microbial reduction was found in processed strawberry juice with ACP coupled-hydrothermal treatment in comparison to control juice ( p  < 0.05). Therefore, ACP treatment of 10 min followed by hydrothermal treatment was found to be advantageous processing for strawberry juice to retain nutritional quality and decrease microbial load. Moreover, further optimization of ACP or hydrothermal processing with utilization of preservatives could be achieved for desired microbial inactivation for an industrial process.